Educação para cidadania digital: conceitos, dimensões e reflexões - Correia, Celise Monteiro França (2021)
This study is part of the research line New Technologies in Education, of the Pontifical Catholic University of São Paulo's Postgraduate Program in Education: Curriculum. It aims to identify the perspective of different authors about digital citizenship in education, from scientific productions in Portuguese language, from 2014 to 2020. The study is of a qualitative approach. To further explore the theme, by means of a Systematic Literature Review, the search was carried out in the Brazilian Digital Library of Theses and Dissertations (BDTD) database, in the Open Access Scientific Repositories of Portugal (RCAAP), and in the Capes Periodical Portal. The collected data were critically analyzed in order to identify the concepts of “digital citizenship”, highlighted by the authors of the research and scientific articles. For data analysis, it´s used a qualitative analysis technological system, the Nvivo12 Software. In the survey, it was identified that there is little research on the subject, which stresses the necessary discussion about digital citizenship in education and the formation of a critical and participatory person, who knows his rights and duties on the Internet and has the awareness and responsibility to browse safely, understanding what is done with his data. And, also, how to be a critical reader when accessing information on the internet, not spreading misinformation